Answer:
f(x) = 2x3 + 4
Stretch vertically be a factor of 2:
f(x) = 2*2x3 + 4 = 4x3 + 4
Shift 5 units to the left:
f(x) = 4(x+5)3 + 4
Step-by-step explanation:
We have been given that David, Egil and Frances share money in the ratio 2:7:9.
Let 2x, 7x and 9x be the amounts of money that David, Agil and Frances get respectively.
We are told that Frances gets $80 more than David. So we can write this information in an equation as:
![9x=2x+80](https://tex.z-dn.net/?f=9x%3D2x%2B80)
Now let us solve for x.
![9x-2x=80](https://tex.z-dn.net/?f=9x-2x%3D80)
![7x=80](https://tex.z-dn.net/?f=7x%3D80)
Now let us substitute
in 7x (amount of money that Egil gets).
![\text{ Amount of money that Egil will get}=7\cdot \frac{80}{7}](https://tex.z-dn.net/?f=%5Ctext%7B%20Amount%20of%20money%20that%20Egil%20will%20get%7D%3D7%5Ccdot%20%5Cfrac%7B80%7D%7B7%7D)
Upon cancelling out 7 from numerator and denominator we will get,
Therefore, Egil will get $80.
Answer:
you need to bring the 8x over then the -3
Step-by-step explanation:
X^2-3x+27=8x-3
X^2-11x+27=-3
x^2-11x+24
Is that what you are looking for??
Hope that helps feel free to ask more questions
Brainliest??
Answer:
![90\pi](https://tex.z-dn.net/?f=90%5Cpi)
Step-by-step explanation:
The first step is to find the slant height of the cone. Using the pythagorean theorem, you can find that
cm. Plugging this into the equation, you get
. Hope this helps!